The role of pannexin hemichannels in inflammation and regeneration - Makarenkova, Helen P.; Shestopalov, Valery I. (Frontiers in Physiology, 2014)
Tissue injury involves coordinated systemic responses including inflammatory response, targeted cell migration, cell-cell communication, stem cell activation and proliferation, and tissue regeneration. The inflammatory response is an important prerequisite for regeneration. Multiple studies suggest that extensive cell-cell communication during tissue regeneration is coordinated by purinergic signaling via extracellular ATP. Most recent data indicates that ATP release for such communication is mediated by hemichannels formed by connexins and pannexins. The Pannexin family consists of three vertebrate proteins (Panx 1, 2, and 3) that have low sequence homology with other gap junction proteins and were shown to form predominantly non-junctional plasma membrane hemichannels. Pannexin-1 (Panx1) channels function as an integral component of the P2X receptor (P2XR) (purinergic) signaling pathway and is arguably the major contributor to pathophysiological ATP release. Panx1 is expressed in many tissues, with highest levels detected in developing brain, retina and skeletal muscles. Panx1 channel expression and activity is reported to increase significantly following injury/inflammation and during regeneration and differentiation. Recent studies also report that pharmacological blockade of the Panx1 channel or genetic ablation of the Panx1 gene cause significant disruption of progenitor cell migration, proliferation, and tissue regeneration. These findings suggest that pannexins play important roles in activation of both post-injury inflammatory response and the subsequent process of tissue regeneration. Due to wide expression in multiple tissues and involvement in diverse signaling pathways, pannexins and connexins are currently being considered as therapeutic targets for traumatic brain or spinal cord injuries, ischemic stroke and cancer. The precise role of pannexins and connexins in the balance between tissue inflammation and regeneration needs to be further understood.